Pengaruh Rasio Keuangan, Growth, Ukuran Perusahaan, dan Inflasi Terhadap Financial Distress di Sektor Pertambangan Yang Terdaftar DI Bursa Efek Indonesia (BEI) Periode 2012-2016 - AYU PERTIWI, DILA (Jurnal Ilmu Manajemen (JIM), 2018)
Financial distress is a condition where the company is experiencing a very bad financial slump for the development of the company, so it will trigger a lot of losses. This study aims to determine what are the factors that affect the occurrence of possible financial distress in a company. This research uses liquidity (CR), leverage (DAR), profitability (ROA), growth ratio (SG), firm size (Ln_Ta) and inflation on financial distress. The sample of this research is 34 companies sector listed in Indonesia stock exchange year 2012-2016. Sample selection using purposive sampling technique. Analytical technique used is logistic regression. The results of this study indicate that ROA and inflation have a negative effect on financial distress, but the proxy of CR, DAR, SG, Ln_TA shows the results do not affect the financial distress in the mining sector companies.Keywords: Financial distress, Financial ratio, growth ratio, firm size and inflation